Log-Spiral Sensor Design to Detect Partial Discharge in Transformer - Herman H Sinaga; Diah Permata; Nining Purwasih; M. Achirul Akbar (Journal of Renewable Energy, Electrical, and Computer Engineering, 2025)
The method of detecting electromagnetic signals generated by partial discharge is a method that is currently developing to detect early damage to Transformers. This method is done by utilizing an antenna that serves as a sensor to capture electromagnetic signals. This paper discusses the design of sensors to detect partial discharge in Transformers. The designed sensor is a planar type which has dual-arms log-spiral. Customized sensor dimensions inspection windows are commonly found on power transformers, with a diameter of 15 cm. With the specified dimensions attached sensor with an impedance of 160 Ohms. Because measuring instruments generally have an impedance of 50 ohms, it takes a balun as a transition from the sensor impedance of 160 Ohms. The designed Balun is a coplanar wave guide - coplanar strip line (cpw-cps) type with 6 of number of transition.